Barriers to treatment of infectious and other somatic comorbidity in drug users - Mravčík, V; Kožený, J; Nečas, V; Tišanská, L (Epidemiologie, mikrobiologie, imunologie, 2020)
BACKGROUND: Intensive use of illicit drugs in general and drug injecting in particular are associated with higher somatic co-morbidity, especially of infectious aetiology. The treatment participation of drug users is complicated by a number of barriers. MATERIAL AND METHODS: At the end of 2013, a cross-sectional questionnaire study was conducted on a non-random sample of 240 drug users (188 men and 52 women) recruited in low-threshold drug services in Prague based on their willingness to participate in the study. Drug injecting sometimes in their lifetime was reported by 237 respondents (98.8%), injecting drug use in the last 12 months by 232 (96.7%), and injecting drug use in the last 30 days by 228 (95.0%). The questionnaire included 38 of the 59 original items from the Barriers to Treatment Inventory (BTI). Factor analysis of these items was performed. In addition to the questionnaire survey, two focus groups with a total of 14 clients were carried out. RESULTS: The factor analysis resulted in a 5-factor model that was fed with 23 BTI items. The factors identified can be interpreted as: (1) difficulty entering treatment due to additional responsibilities (e.g. children, family, work, etc.), (2) previous poor treatment experience, fear and concerns about the treatment or negative attitudes of staff, (3) financial difficulties and formal barriers (health insurance debts, problems with the law, etc.), (4) concerns that entering treatment will be too complicated and difficult, (5) distrust of the treatment's ability to improve the client's life situation. The results of the focus groups have shown that drug users face stigmatization and discrimination in healthcare facilities. CONCLUSION: The access to treatment of infectious and other somatic co-morbidity in drug users is complicated by a number of barriers, which largely arise from the lifestyle and socio-economic situation associated with drug use and from negative experiences with the attitude of medical staff. Healthcare professionals should actively identify and respond to barriers to care among drug users by taking appropriate measures in the context of a multidisciplinary approach and cooperation.
Keywords: poruchy spojené s užíváním psychoaktivních látek; Comorbidity; infectious diseases; Humans; lidé; drug use; komorbidita; infekční nemoci; barriers to care; somatic comorbidity; Female; Male; Drug Users; mužské pohlaví; ženské pohlaví; Cross-Sectional Studies; Communicable Diseases; průřezové studie; uživatelé drog; Substance-Related Disorders; injecting drug use